2017
DOI: 10.1128/jvi.01443-16
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-electron Microscopy Structures of Expanded Poliovirus with VHHs Sample the Conformational Repertoire of the Expanded State

Abstract: By using cryo-electron microscopy, expanded 80S-like poliovirus virions (poliovirions) were visualized in complexes with four 80S-specific camelid VHHs (Nanobodies). In all four complexes, the VHHs bind to a site on the top surface of the capsid protein VP3, which is hidden in the native virus. Interestingly, although the four VHHs bind to the same site, the structures of the expanded virus differ in detail in each complex, suggesting that each of the Nanobodies has sampled a range of low-energy structures ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 49 publications
4
23
0
Order By: Relevance
“…Specifically, in comparison to full virus capsids, the first 60 amino acids in the N terminus of VP1 of the early RNArelease structures were disordered [7][8][9][10][11]34]. While in a more recent study of Poliovirus, the VP1 N terminus was observed to be rearranged [18]. Three of the seven enteroviruses mapped in this study correspond to structures in these previous studies, including Enterovirus 71 [7], Coxsackievirus A9 [20] and Rhinovirus A2 [23].…”
Section: Extensive Network Of Protein Interactions Are Conserved Witsupporting
confidence: 51%
See 3 more Smart Citations
“…Specifically, in comparison to full virus capsids, the first 60 amino acids in the N terminus of VP1 of the early RNArelease structures were disordered [7][8][9][10][11]34]. While in a more recent study of Poliovirus, the VP1 N terminus was observed to be rearranged [18]. Three of the seven enteroviruses mapped in this study correspond to structures in these previous studies, including Enterovirus 71 [7], Coxsackievirus A9 [20] and Rhinovirus A2 [23].…”
Section: Extensive Network Of Protein Interactions Are Conserved Witsupporting
confidence: 51%
“…The externalisation of the N terminus of VP1 and complete loss of VP4 was observed in all RNA-release intermediates reported. While in a more recent study of Poliovirus, the VP1 N terminus was observed to be rearranged [18]. While in a more recent study of Poliovirus, the VP1 N terminus was observed to be rearranged [18].…”
Section: Extensive Network Of Protein Interactions Are Conserved Witmentioning
confidence: 87%
See 2 more Smart Citations
“…Trapping the particles in a particular conformation or otherwise inhibiting capsid "breathing" is a common antiviral strategy shared by many neutralizing mAbs, Nanobodies, and drugs against HIV, flaviviruses, picornaviruses, influenza, and others [54][55][56][57][58][59][60]. For example, several neutralizing Nanobodies against poliovirus and respiratory syncytial virus were shown to specifically stabilize either the native or expanded conformation of capsid, preventing it from further rearrangement necessary for the infection process [30,61]. It is plausible that in the case of norovirus Nanobodies described here, binding resulted in a stabilization of the particular P domain conformation, thus reducing the mobility and influencing the position on the S domain.…”
Section: Discussionmentioning
confidence: 99%